2017
DOI: 10.12659/msm.903377
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Importance of Somatostatin Receptor 2 (SSTR2) and Somatostatin Receptor 5 (SSTR5) Expression in Thyrotropin-Producing Pituitary Adenoma (TSHoma)

Abstract: BackgroundThyrotropin-secreting pituitary adenomas (TSHomas) are a rare cause of hyperthyroidism. Somatostatin analogs have proved to be effective for inhibiting pituitary hormones secretion, working via interactions with somatostatin receptors (SSTRs). Moreover, antiproliferative activity of somatostatin analog is now demonstrated in several studies. In the present study, we determined the relative predominance of SSTR2 and SSTR5 subtypes among the different types of adenomas, especially TSHoma, and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…SSAs were originally used to control high level of GH in acromegaly patients. SSAs stimulate p27 expression and inhibit the MAPK pathway in pituitary tumors by binding to SSRT2 and SSRT5 [ 17 19 ].Studies have found that SSTR2 and SSTR5 also express in TSHoma cells, suggesting that SSAs can be used to treat TSHoma [ 8 , 9 ]. The secretion of TSH is mediated through the interactions between SSAs and SSRT2, whereas the reduction in tumor size is influenced mainly by the interactions between SSAs and SSRT5 [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…SSAs were originally used to control high level of GH in acromegaly patients. SSAs stimulate p27 expression and inhibit the MAPK pathway in pituitary tumors by binding to SSRT2 and SSRT5 [ 17 19 ].Studies have found that SSTR2 and SSTR5 also express in TSHoma cells, suggesting that SSAs can be used to treat TSHoma [ 8 , 9 ]. The secretion of TSH is mediated through the interactions between SSAs and SSRT2, whereas the reduction in tumor size is influenced mainly by the interactions between SSAs and SSRT5 [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this test, the TRH stimulation test and TSH-oma are applied when the differential diagnosis of thyroid hormone resistance is not made. In this test, the absence of suppression in TSH is interpreted in favor of TSHoma, and the presence of TSH suppression in favor of thyroid hormone resistance [22]. In addition, TSH suppression can be measured using somatostatin analogues.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is the gold standard treatment for TSHoma. Post-surgical remission rate is between 35-58% [1,22,24]. Preoperative medical treatment can be initiated in patients to increase remission after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The somatostatin suppression test contributes to the diagnosis and differential diagnosis of TSH-oma. Because the somatostatin receptor is expressed on the surface of TSH-oma cells ( 22 ), the secretion of TSH could be inhibited after somatostatin analog injection in patients with TSH-oma. The TSH suppression rate was calculated by the proportion of the largest decrease in the initial TSH level.…”
Section: Discussionmentioning
confidence: 99%